The principle of tolerance in Rudolf Carnap and his pragmatist interpretation - Morollón Del Río, Diego (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2018)
In this paper we will explain the Principle of Tolerance in Rudolf Car-nap and its relation with some values and pragmatism that are sup-posed in this principle. The intention is to do a introductory summary to understand the bases of the Principle of Tolerance. This bases will end in pragmatic premises that include Ilustrated values in the exer-cise of science. This values will help us to choose between scientific systems (like mathematics in Newton or Einstein theories, or euclid-ean or non-euclidean geometrics) that are logical but they are choose because of their pragmatic use. This hipothesys will be ac-cording with the interpretation of A. W. Carus, and represents some now perspective of Rudolf Carnap.